Litigating Sex Discrimination Cases in the 1970s - Rabb, Harriet S. (Columbia Journal of Gender and Law, 2013)
Title VII of the Civil Rights Act of 1964 made it unlawful for an employer to hire or fire an employee or to discriminate by classifying, compensating, or denying opportunity to an employee on the basis of race, color, religion, sex, or national origin. Sex as a protected category was an afterthought. The bill was opposed by many in Congress, among them a Virginia representative who caused the bill to be amended to add sex- perhaps expecting that the protection of women-workers would result in killing the bill. Another Congressman proposed that a woman should not be permitted to claim sex discrimination unless she filed a sworn statement that her spouse was unemployed. Those maneuvers failed, and the Act passed. It went into effect on July 1, 1965. Though Title VII promised women equality of employment opportunity, even many supporters of women’s rights were committed to protecting women as workers while preserving their traditional roles as wives and mothers. I recommend to you the scholarship of Cary Franklin for a wonderful and illuminating look back at these times.